Theoretical Underpinnings of India–Pakistan Relations. (June 2020) - Shukla, Ashish
The India–Pakistan relations have historically been marked by mistrust, broken promises, unresolved issues and unending conflicts. A number of divisive factors shaped and influenced the nature of this relationship which inter alia includes large-scale violence at the time of partition, perceptual enmity and numerous unresolved issues including Kashmir. Due to all these reasons, the two countries have found themselves locked in a complex situation that could best be described using zero-sum two-person game. The author argues that perceptions play an important role in shaping the nature of bilateral relations. He goes on to identify six different prisms—three each in India and Pakistan—through which one can understand the nature and direction of this otherwise difficult relationship.